The relationship between match performance indicators and outcome in Australian Football - Young, C. M.; Luo, W.; Gastin, P.; Tran, J.; Dwyer, D. B. (Journal of Science and Medicine in Sport, 2019)
Objectives: To identify novel insights about performance in Australian Football (AF), by modelling the relationships between player actions and match outcomes. This study extends and improves on previous studies by utilising a wider range of performance indicators (PIs) and a longer time frame for the development of predictive models.